Always bad for creativity? An affect-based model of job insecurity and the moderating effects of giving support and receiving support. (August 2019) - Teng, Eryue; Zhang, Li; Qiu, Yang
Drawing on an overarching framework of transactional stress theory, in this article the authors develop and test a theoretical model specifying the affect-based relationships between job insecurity and employee creativity, as well as the buffering role of giving support and receiving support in the affective processes. Results from a sample of 569 employees showed that job insecurity had offsetting indirect links with employee creativity through attentiveness and irritation. Both giving support and receiving support reduce the negative effect of job insecurity on employee creativity because they both weaken the negative link between job insecurity and irritation. It was also found that receiving support enhanced the positive relationship between job insecurity and attentiveness. Implications of the results to theory and practice are discussed.